GaAsSb/InGaAs heterojunction tunnel field-effect transistors with a heterogeneous channel. (7th February 2018) - Lin, Chun-Wei; Chen, Hung-Ru; Yu, Yu-Tzu; Hsin, Yue-Ming
Abstract: This study presents a new structure to improve off-state current and ambipolar conduction in GaAsSb/InGaAs heterojunction tunnel field-effect transistors (HTFET). A GaAsSb/InGaAs heterogeneous channel was proposed to form p-GaAsSb/i-InGaAs junction at the source side and i-GaAsSb/n-InGaAs junction at the drain side. In the off-state bias condition, the band offsets of GaAsSb/InGaAs in the channel can prevent electrons tunneling to the drain side to reduce the leakage current and ambipolar conduction. Through simulation, heterogeneous channel HTFETs demonstrate that the off-state current can be reduced by four orders of magnitude and still demonstrate a high on-state current compared with GaAsSb/InGaAs HTFETs. As a result, the proposed heterogeneous channel HTFET exhibits suppressed ambipolar conduction even when the drain doping is as high as 1 × 10 19 cm −3 .